Generativity as a Route to Active Ageing. (7th August 2012) - Kruse, Andreas; Schmitt, Eric
Abstract : We elucidate the significance of active ageing from an individual as well as from a societal perspective. Taking an individual perspective, maintaining activity in later years is linked to successful ageing because of empirical relationships to positive self-perception, satisfaction with life, and development of competences, whereas from a societal perspective, active ageing implies usage of older people's life competences as a human capital of society—a societal imperative, particularly in times of demographic change but also more basically substantiated in an ethics of responsibility, intergenerational solidarity, and generation equity. We focus on the psychological construct of generativity which is interpreted as an aspect of the philosophical-anthropological category of joint responsibility. Our own research in Mexico and the Baltic States supports the notion that maintaining access to the public sphere and active engagement for others is a more basic individual concern than a life-stages specific developmental task. We report background and results of a Dialogue Forum Project Funding, a research cooperation between our institute and the Foundation Remembrance, Responsibility, and Future aimed to improve generativity in Belarus, Russia, and Ukraine by implementing and supporting local initiatives offering opportunities for intergenerational dialogue.